Influence of implementation of face recognition absence on employee work discipline - Aqfir, Aqfir; Sabran.A, Moh.; Ilham, Ilham (FEB Universitas Mulawarman, 2023)
This study aims to determine and analyze the effect of implementing face recognition attendance on employee work discipline at the Office of the Ministry of Religion, Tolitoli Regency. The population The population of this study were all civil servants at the Office of the Ministry of Religion of Tolitoli Regency, totaling 76 people. The sampling technique used in this study was saturated sampling technique (census) in which all members of the population were used as respondents in this study, namely all civil servants of the Office of the Ministry of Religion of Tolitoli Regency totaling 76 employees. The tool used in proving the hypothesis is simple linear regression. The results of the research on the effect of applying face recognition absences on employee work discipline at the Office of the Ministry of Religion of Tolitoli Regency show that the application of face recognition attendance has a significant effect on employee work discipline at the Office of the Ministry of Religion of Tolitoli Regency. The coefficient of determination R2 or RSquare Which obtained by 0.450. This shows that the magnitude of the effect of applying face recognition attendance on employee work discipline is 45.0% while the remaining 55.0% is influenced by other variables.